2002
DOI: 10.1046/j.1365-2885.2002.00400.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of body composition on the pharmacokinetics of subcutaneously injected ivermectin and moxidectin in pigs

Abstract: Macrocyclic lactones are characterized by their long persistence in animals because of their extensive distribution into fat. This study examined the influence of body condition on the disposition of ivermectin (IVM) and moxidectin (MXD) in blood and fat following subcutaneous (s.c.) drug administration. 'Fat' and 'thin' lines of pigs were established using two different diets. All animals were then injected with either MXD or IVM at 300 microg/kg and blood samples were taken at regular intervals until slaught… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
44
1
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 13 publications
2
44
1
1
Order By: Relevance
“…For lipophilic macrocyclic lactones such as moxidectin and ivermectin, subcutaneous fat is likely to influence drug absorption (Oksanen et al, 1995), and these drugs are preferentially distributed into adipose tissue which may act as a drug reservoir and facilitate persistence (Zulalian et al, 1994). In domestic pigs, for example, persistence of macrocyclic lactones is strongly influenced by body condition, with both ivermectin and moxidectin less persistent in thin compared with fat animals (Craven et al, 2002). This might explain why moxidectin is effective in wild Svalbard reindeer at far lower dosages (0.4 mg/kg) than used in this study, as reindeer accumulate large amounts of subcutaneous back fat (Irvine, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…For lipophilic macrocyclic lactones such as moxidectin and ivermectin, subcutaneous fat is likely to influence drug absorption (Oksanen et al, 1995), and these drugs are preferentially distributed into adipose tissue which may act as a drug reservoir and facilitate persistence (Zulalian et al, 1994). In domestic pigs, for example, persistence of macrocyclic lactones is strongly influenced by body condition, with both ivermectin and moxidectin less persistent in thin compared with fat animals (Craven et al, 2002). This might explain why moxidectin is effective in wild Svalbard reindeer at far lower dosages (0.4 mg/kg) than used in this study, as reindeer accumulate large amounts of subcutaneous back fat (Irvine, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the sample preparation, most procedures described for MOX residue quantitation in plasma involve clean up steps using solid phase microextraction cartridges (SPME) 8,[11][12][13] and derivatization step. According to literature, the pharmacokinetic (PK) parameters of a veterinary drug vary according to the applied dose, animal species, type of animal and the application site, among others.…”
Section: Introductionmentioning
confidence: 99%
“…2, 2017 step. [8][9][10][11][12][13] Rarely are described analytical methods by using mass spectrometry as a detector for MOX.14 However, it is important to emphasize that analytical methods based on liquid chromatography coupled to mass spectrometry (HPLC-MS) are sufficiently sensitive and selective to quantify the compounds in very low amounts, not being necessary a derivatization step.Regarding the sample preparation, most procedures described for MOX residue quantitation in plasma involve clean up steps using solid phase microextraction cartridges (SPME) 8,11-13 and derivatization step. According to literature, the pharmacokinetic (PK) parameters of a veterinary drug vary according to the applied dose, animal species, type of animal and the application site, among others.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, combinations of drugs can sometimes be used in conjunction with the knowledge of local epidemiology of parasites to reduce the frequency of treatment and further reduce exposure of the worms to the anthelmintics. It has been shown that the clinical effectiveness of anthelmintics is closely related to their pharmacokinetic profiles (Bassisi et al, 2004;Bogan and McKellar, 1988;Toutain et al, 1988;Craven et al, 2002).…”
Section: Introductionmentioning
confidence: 99%